Effects of combined helium pre/post‐conditioning on the brain and heart in a rat resuscitation model. Issue 1 (20th November 2017) - Aehling, C.; Weber, N. C.; Zuurbier, C. J.; Preckel, B.; Galmbacher, R.; Stefan, K.; Hollmann, M. W.; Popp, E.; Knapp, J.
Abstract : Background: The noble gas helium induces cardio‐ and neuroprotection by pre‐ and post‐conditioning. We investigated the effects of helium pre‐ and post‐conditioning on the brain and heart in a rat resuscitation model. Methods: After approval by the Animal Care Committee, 96 Wistar rats underwent cardiac arrest for 6 min induced by ventricular fibrillation. Animals received 70% helium and 30% oxygen for 5 min before cardiac arrest and for 30 min after restoration of spontaneous circulation (ROSC). Control animals received 70% nitrogen and 30% oxygen. Hearts and brains were excised after 2, 4 h or 7 days. Neurological degeneration was evaluated using TUNEL and Nissl staining in the hippocampal CA‐1 sector. Cognitive function after 7 days was detected with the tape removal test. Molecular targets were measured by infrared western blot. Data are shown as median [Interquartile range]. Results: Helium treatment resulted in significantly less apoptosis (TUNEL positive cells/100 pixel 73.5 [60.3–78.6] vs.78.2 [70.4–92.9] P  = 0.023). Changes in Caveolin‐3 expression in the membrane fraction and Hexokinase‐II in the mitochondrial fraction were observed in the heart. Caveolin‐1 expression of treated animals significantly differed from control animals in the membrane fraction of the heart and brain after ROSC. Conclusion: Treatment with helium reduced apoptosis in our resuscitation model. Differential expression levels of Caveolin‐1, Caveolin‐3 and Hexokinase II in the heart were found after helium pre‐ and post‐conditioning. No beneficial effects were seen on neurofunctional outcome.